2018
DOI: 10.56093/ijas.v88i11.84913
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of different integrated farming system models for small and marginal farmers under the Eastern Himalayas

Abstract: Integrated farming system (IFS) ensures efficient utilization of available farm resources, increases unit productivity and income that are pre-requisite for sustainable livelihood of small and marginal farmers. The present study was conducted to evaluate the performance of four IFS model developed in ~ 1.0 acre area, at ICAR Research Complex for North Eastern Hill Region, Nagaland Centre, Jharnapani, Medziphema, Nagaland. The major components in IFS models were agriculture, horticulture, livestock and subsidia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…To address these emerging issues, there is a need for problemsolving production approaches that not only ensure a continuous supply of various commodities to a family/nation but also recycle the wastes, maintaining an ecological balance and sustaining the resources for the future generation (Palsaniya et al, 2022;Patel et al, 2019). In this regard, an IFS is an eco-friendly approach that is a suitable combination of farm enterprises allocated systematically in the farm which perform synergistically among themselves and the produce available to the farmer is utilized by the family for their food and nutritional security to sustain their livelihood (Kumar et al, 2018). Walia et al (2019) defined integrated farming as a biologically integrated system, which integrates natural resources in a regulated mechanism into farming activities to achieve maximum replacement of offfarm inputs and sustain farm income.…”
Section: Needs and Componentsmentioning
confidence: 99%
See 3 more Smart Citations
“…To address these emerging issues, there is a need for problemsolving production approaches that not only ensure a continuous supply of various commodities to a family/nation but also recycle the wastes, maintaining an ecological balance and sustaining the resources for the future generation (Palsaniya et al, 2022;Patel et al, 2019). In this regard, an IFS is an eco-friendly approach that is a suitable combination of farm enterprises allocated systematically in the farm which perform synergistically among themselves and the produce available to the farmer is utilized by the family for their food and nutritional security to sustain their livelihood (Kumar et al, 2018). Walia et al (2019) defined integrated farming as a biologically integrated system, which integrates natural resources in a regulated mechanism into farming activities to achieve maximum replacement of offfarm inputs and sustain farm income.…”
Section: Needs and Componentsmentioning
confidence: 99%
“…This holistic approach creates a broad spectrum of opportunities for rural livelihood and tackles the environmental problems caused by prevailing systems, thus showcasing its potential to enhance agricultural output across the different regions of India. Farmers can adopt different components along with suitable crops to get higher system productivity with higher profitability and employment from the same piece of land (Kumar et al, 2018). Moreover, Kaur, Prusty, et al (2021); Kaur, Vashist, et al (2021) stated that systematically planned interventions, addressing identified constraints in different components of farming systems lead to an increase in farmers' net income.…”
Section: System Productivity Profitability and Employment Generation ...mentioning
confidence: 99%
See 2 more Smart Citations
“…Such integration of these various parts has proven to be profitable [9], productive and sustainable [10,11]. This integrated agriculture is one of the resource management strategies that can increase production, be economical and sustainable [12,13].…”
Section: Integrated Farmingmentioning
confidence: 99%